Experimental Dining Performance, Experience and Ideology in Contemporary Creative Restaurants. - Geary, Paul (Intellect Books Ltd, 2021)
Considers four of the world's leading creative restaurants as experimental performance practice. Using ideas from performance studies, cultural studies, philosophy and economics, the book argues that technoemotional restaurants can be understood as both a commodified experience and an artistic and aesthetic practice. 10 b/w photographs.